The Effects of a Classroom Communication System on Third-Grade Student Engagement in Learning Mathematics - Fore, Aleph (Valdosta State University, 2006)
The purpose of this action research study was to investigate the effect a classroom communication system (CCS) had on teaching and learning in third-grade mathematics instruction. Examinations of student-engagement and teacher experiences were conducted. The examinations revealed an overall acceptance of CCS as an effective instructional technology that improved student engagement.
Keywords: classroom communication system; mathematics; instructional technology; Educational technology; Teaching--Aids and devices